Site-specific Tn7 transposition into the human genome - Kuduvalli, Prasad N. (Oxford University Press, 2005)
The bacterial transposon, Tn7, inserts into a single site in the Escherichia coli chromosome termed attTn7 via the sequence-specific DNA binding of the target selector protein, TnsD. The target DNA sequence required for Tn7 transposition is located within the C-terminus of the glucosamine synthetase (glmS) gene, which is an essential, highly conserved gene found ubiquitously from bacteria to humans. Here, we show that Tn7 can transpose in vitro adjacent to two potential targets in the human genome: the gfpt-1 and gfpt-2 sequences, the human analogs of glmS. The frequency of transposition adjacent to the human gfpt-1 target is comparable with the E.coli glmS target; the human gfpt-2 target shows reduced transposition. The binding of TnsD to these sequences mirrors the transposition activity. In contrast to the human gfpt sequences, Tn7 does not transpose adjacent to the gfa-1 sequence, the glmS analog in Saccharomyces cerevisiae. We also report that a nucleosome core particle assembled on the human gfpt-1 sequence reduces Tn7 transposition by likely impairing the accessibility of target DNA to the Tns proteins. We discuss the implications of these findings for the potential use of Tn7 as a site-specific DNA delivery agent for gene therapy.